Age dependence of excitatory-inhibitory balance following stroke - Schmidt, Silvio; Bruehl, Claus (Neurobiology of aging, 2012)
The mechanisms which mediate cortical map plasticity and functional recovery following stroke remain a matter of debate. Readjustment of the excitatory-inhibitory balance may support cortical map plasticity in perilesional areas. Here we studied cortical net inhibition in the vicinity of photothrombotically-induced cortical lesions in young adult (3 months) and aged (24 months) male rats. Field potentials were recorded in cortical layer II/III following application of paired-pulse stimulation at layer VI/white matter in coronal brain slices. Additionally, we analyzed the regional distribution of 5 major gamma-aminobutyric acid A (GABAA) receptor subunits (α1, α2, α3, α5, and γ2) by immunohistochemistry. Paired-pulse inhibition in the perilesional parietal cortex was decreased in young rats but was increased in aged rats. As a consequence of the diminished intrinsic net inhibition in aged control animals, the excitatory-inhibitory balance was readjusted to an age-independent similar level in young and aged lesioned rats in a homeostatic-like fashion. These physiological changes in neuronal activity were accompanied by age-specific laminar alterations of the gamma-aminobutyric acid A (GABAA) receptor subunit composition, most prominently of the subunit α5. The present study suggests that the mechanisms underlying functional reorganization in aged animals may be distinctly different from those in young animals.